Contribuições do saber filosófico para a formação ética e prática do docente de atendimento educacional especializado - Santos, Márcia Cristina Machado Oliveira (2016)
This research aimed to apprehend primarily possibilities, limits, actions and functions of the philosophical knowledge for ethics and practical teachers’ training of Educational Support Services Specialized (AEE), the Association of Parents and Friends of Exceptional Children (APAE) of Goiania. The central question of this study was to investigate whether initial training courses for teachers take into account the ethics of teaching and what consequences it brings to the practice of teaching students with disabilities. To understand and respond to this question, the concepts of ethics in Kant and Defectology in Vygotsky were taken as references, along with the Laws that conduct the Special Education in Brazil. Due to its characteristics, this research was called applied quantitative and qualitative nature (LUDKE; ANDRÉ, 1986), with bibliographical sources, document analysis and questionnaires. First, the training in higher education of the AEE teachers from the APAE of Goiânia was identified and subsequently conducted a data survey of the Pedagogical Political Project and their graduation and specialization courses in order to realize the presence or not of the philosophical and ethical training in their curricula as well as teaching professional profile desired. The total of eighteen professionals who make up the AEE framework of APAE/Goiânia 13 participated (seven teachers, five graduates in Physical Education and an audiologist ) which responded to the three blocks of questions about ethics and its make daily school. The results were presented through graphs and charts, and analyzes raised that although the theme "Ethics" is not linear and clearly specified in the PPC's of their courses, these teachers consider very important the contributions of philosophical knowledge to professional ethics training, and they expressed concern over an ethical school for students with disabilities. Therefore it was possible to consider that the values, the ethical behavior of each individual are seized from stimuli issued by the family, peer groups, beyond the formal school environment. It is noteworthy the considerations of the teachers refer to think of a philosophy in constant dialogue with the practice, with the classroom with the student. In this response teachers indicated ethical values present in their actions and towards the learning and development of their pupils, emphasizing respect for differences; respect for the student, the family, culture and disability; responsibility and commitment to the work. Providing think that ethics is inclusion, is to recognize the students as subjects, considering the human being, consisting of desire, needs, potentials and limits and not to enhance the disabilities. Concluding it can be said that the ethics and teacher training are now issues that are at stake, so it is necessary to consider how they belong in the process of training and teaching practice, because the teaching profession requires attitudes, decisions and actions that have ethical implications. The teacher needs to be more attentive and prepared to ethical issues, because he often faces dilemmas, decisions, rights of them and students. Ethics is a content of philosophy, is a knowledge facing the "must- be" in this sense, it is important to support the concepts and the actions of teachers. And as a result of this investigation, which qualifies a applied research in the chapter entitled Ethics and Continuing Education in APAE is a proposal for a study group aiming to contribute to this ongoing transformation.